Implementation of ISAK NO.35 on Non-Profit Organizations as an Evaluation of the Financial Report of the Indonesian Red Cross (PMI) of Medan City: Auditability, Transparency and Performance - Azzahra, Nisa; Harmain, Hendra; Syafina, Laylan (Universitas Islam Lamongan, 2024)
This study investigates the implementation of ISAK No. 35 in the financial reporting of UDD PMI Medan City, focusing on auditability, transparency, and performance. The study was conducted at UDD PMI Medan City located in East Medan, Medan, due to its important role in the metropolitan area. Data were collected through in-depth interviews with key personnel and documentation of financial activities. The study found that the implementation of ISAK No. 35 improves the transparency and accountability of financial statements, which include the statement of financial position, statement of comprehensive income, changes in net assets, statement of cash flows, and notes to the financial statements. Compliance with ISAK No. 35 ensures that financial reporting provides a clear and accurate picture of the financial health and performance of UDD PMI Medan City, increasing public trust and facilitating better financial management and decision making. The results of the study indicate that the financial statements of UDD PMI Medan City are in accordance with ISAK No. 35, which significantly contributes to improving financial transparency and accountability